PRICE-COST SQUEEZE AND SMALLHOLDER PRODUCTION DISINCENTIVES: EMPIRICAL EVIDENCE FROM KATSINA STATE, NIGERIA - Abbas, A.; Sani, A.; Gusau, S. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the production disincentive effect arising from the interaction between output price crashes and input cost inflation among smallholder farmers in Katsina State, Nigeria. The objectives of the study were to assess the extent of output price declines across major staple crops, examine the structure of rising input costs, determine the relationship between price crashes and subsequent-season production decisions, and identify socioeconomic factors moderating the disincentive effect. A mixed-methods cross-sectional design with a retrospective panel component was employed. Primary data were collected from 400 smallholder households selected through multi-stage stratified random sampling across 13 Local Government Areas. Data were analyzed using gross margin analysis and seemingly unrelated regression (SUR). Farm-gate prices declined across all major staple crops: maize by 55%, sorghum by 60%, millet by 47.6%, and cowpea by 46.1%, while input costs rose by 75–154.5%. Gross margin collapsed from ₦820,000 to −₦480,000 per hectare. SUR estimates confirm that output price declines significantly reduced fertiliser expenditure (β = −0.428, p < 0.001), cultivated area (β = −0.316, p < 0.001), and seed expenditure (β = −0.284, p < 0.01). In conclusion, the price-cost squeeze has rendered smallholder farming economically unviable in northern Katsina State. Without price stabilisation mechanisms, targeted input subsidies, and rural market infrastructure investment, agricultural sustainability in semi-arid northern Nigeria faces serious long-term threats.